Kinds of Mathematical Thinking Addressed in Geometry Research in Schools: A Systematic Review - Fachrudin, Achmad Dhany; Juniati, Dwi (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2023)
Geometry is one of the content of mathematics which in many studies is associated with students' thinking abilities, such as critical thinking and reasoning abilities or others..This study aims to conduct a systematic review of the geometry research in school for identifying the types of mathematical thinking and their interconnections. We searched the Scopus database for articles published from 2003 to 2023 using relevant keywords. We applied the PRISMA method to select and evaluate the studies or articles based on the empirical data. We retrieved and evaluated data from the studies on the various styles of mathematical thinking evolved. Out of 166 titles that were initially obtained, only 10 titles passed the five stages of the systematic review protocol process. We identified 10 types of mathematical thinking that were discussed in the context of learning geometry at school: Creative Mathematical Reasoning (CMR), Computational thinking, Geometric reasoning, Geometric thinking van hiele theory, Geometric thinking (3D geometric thinking with representations), 3D geometry thinking, Visuo spatial reasoning, Geometry Spatial Reasoning, mathematical creative reasoning (MCR), and Inductive reasoning. We also found some connections of literature between these types of mathematical thinking, such as CMR and MCR, Geometric reasoning and Geometric thinking, and Visuo spatial reasoning and Geometry Spatial Reasoning. This systematic review provides an overview of the current state of research on geometry and reasoning in school mathematics and reveals some gaps and directions for future study. It also has implications for teachers who want to enhance their students’ mathematical thinking skills in geometry by exposing them to different types of mathematical thinking and their connections.